Extrication following a motor vehicle collision: a consensus statement on behalf of The Faculty of Pre-hospital Care, Royal College of Surgeons of Edinburgh - Tim Nutbeam; Rob Fenwick; Charlotte Haldane; Caroline Leech; Emily Foote; Simon Todd; David Lockey (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Road traffic injury is the leading cause of death among young people globally, with motor vehicle collisions often resulting in severe injuries and entrapment. Traditional extrication techniques focus on limiting movement to prevent spinal cord injuries, but recent findings from the EXIT project challenge this approach. This paper presents updated recommendations from the Faculty of Pre-Hospital Care (FPHC) that reflect the latest evidence on extrication practices. Methods A systematic scoping review identified 170 relevant articles from 7083 records. Findings, together with EXIT project data, informed the development of 12 core and supplemental statements on extrication. In April 2024, 43 subject matter experts from diverse backgrounds participated in a consensus process. Statements were discussed, voted on, and synthesised into the updated statement, ratified by FPHC. Results Consensus was achieved for all 12 statements, emphasising self-extrication as a preferred, primary approach, reducing extrication time, and moving away from absolute movement minimisation. The U-STEP OUT algorithm was endorsed as a decision-making tool. Key themes included interdisciplinary collaboration, use of operational and clinical decision aids, and enhanced training. Conclusions This consensus statement marks a paradigm shift in extrication practice, moving away from traditional movement minimisation to a focus on time-sensitive, patient-centred care. The findings advocate for empowering both clinical and non-clinical responders and improving interdisciplinary training and communication. Further research is needed to assess the broader implementation of this statement and to explore the psychological impacts of entrapment and extrication on patients.